2019
DOI: 10.1101/556084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conjugated linolenic fatty acids trigger ferroptosis in triple-negative breast cancer

Abstract: Recent studies have shown that cancer cells, including renal cell carcinoma, melanoma and glioblastoma are vulnerable to ferroptosis [10][11][12][13][14][15][16] . Furthermore therapy-resistant mesenchymal cancer cells exhibit a greater reliance on GPX4 activity for survival 10,17 . These findings have highlighted the therapeutic potential of pro-ferroptotic agents, but it remains unclear whether induction of ferroptosis can be used therapeutically to selectively kill cancer cells in vivo 1 . A major challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
1
7
1
Order By: Relevance
“…Beatty et al found that the conjugated linoleic acid (LA) α-eleostearic acid induced ferroptosis in TNBC, depending on acyl-CoA synthetase long-chain isoforms other than glutathione or GPX4 activity. In contrast to the previous study, the authors highlighted that three conjugated double bonds in the conjugated LA were required for ferroptotic activity, while their positioning and stereochemistry were less important [82].…”
Section: Ferroptotic Regulators In Breast Cancercontrasting
confidence: 83%
See 1 more Smart Citation
“…Beatty et al found that the conjugated linoleic acid (LA) α-eleostearic acid induced ferroptosis in TNBC, depending on acyl-CoA synthetase long-chain isoforms other than glutathione or GPX4 activity. In contrast to the previous study, the authors highlighted that three conjugated double bonds in the conjugated LA were required for ferroptotic activity, while their positioning and stereochemistry were less important [82].…”
Section: Ferroptotic Regulators In Breast Cancercontrasting
confidence: 83%
“…Apoptosis and ferroptosis can be induced by a common mechanism in breast cancer. As described above, PUFAs can induce ferroptosis in an ACSL4-dependent manner, and induce apoptosis via the peroxisome proliferator-activated receptor gamma (PPARγ)/SDC-1 pathway [82,115]. Lipid peroxidation is the main killer in the process of ferroptosis, which could derive from lipids by being "attacked" by intracellular ROS [18].…”
Section: Apoptosismentioning
confidence: 99%
“…5d). Recent work showed that exogenous PUFAs can sensitize triple negative breast cancer to ferroptosis [77]. If not enzymatically repaired by GPX4 at the expense of reduced glutathione, accumulation of lipid hydroperoxides can lead to cell death via ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the diversity of targeted therapies causing this shared GPX4 dependence suggests that lipid remodeling leading to PUFA enrichment of phospholipids might be a common mechanism associated with therapy resistance that could be pursued as therapeutic target in multiple types of cancer. However, the treatment window of therapy-induced ferroptosis hypersensitivity is likely to be restricted to the low cycling, quiescence phase [9] because high membrane PUFA levels sensitize to ferroptosis [77] and would limit proliferation rates [48] due to the increased lipid peroxidation stress generated by higher metabolic activities and associated ROS production. Such stress would be further aggravated by higher demands in reducing power (NADPH) for the recycling of oxidized glutathione and de novo lipid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that, instead of promoting pathological lipid peroxidation, ExoU might actually use cellular lipid peroxidation to promote cell necrosis. To this regard, various host phospholipase A2 enzymes have been described to specifically cleave and remove peroxidised phospholipids from membranes [60][61][62]. To address this hypothesis, we performed a redox phospholipidomic approach to determine if ExoU could interfere with the endogenous levels of peroxidised phospholipids (Figs 3B and S3C).…”
Section: Plos Pathogensmentioning
confidence: 99%